2006
DOI: 10.1063/1.2400090
|View full text |Cite
|
Sign up to set email alerts
|

Structure and photoluminescence properties of evaporated GeOx∕SiO2 multilayers

Abstract: To cite this version:M. Ardyanian, H. Rinnert, M. Vergnat. Structure and photoluminescence properties of evaporated GeO[sub x]∕ SiO[sub 2] multilayers.Amorphous GeO x / SiO 2 multilayers were prepared by successive evaporations of GeO 2 and SiO 2 powders onto substrates maintained at 100°C. The evolution of the structure was investigated by x-ray reflectometry, transmission electron microscopy, infrared-absorption spectrometry and Raman spectrometry for annealing temperatures less than 800°C. These experiments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
14
0
9

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 17 publications
3
14
0
9
Order By: Relevance
“…Our group has recently prepared amorphous SiO x [14] and GeO x [15,16] thin films by the evaporation of SiO or GeO 2 powder. The as-deposited samples are substoichiometric and thermal treatments provoke a decomposition phenomenon with the apparition of silicon or germanium aggregates growing with increasing annealing temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Our group has recently prepared amorphous SiO x [14] and GeO x [15,16] thin films by the evaporation of SiO or GeO 2 powder. The as-deposited samples are substoichiometric and thermal treatments provoke a decomposition phenomenon with the apparition of silicon or germanium aggregates growing with increasing annealing temperature.…”
Section: Introductionmentioning
confidence: 99%
“…The last two components are more volatile, but, unlike O 2 , GeO is easily deposits onto cool substrate. So, the deposited germanium oxide is substoichiometric, namely GeO x , where x is close to 1 [7]. In [7], it was shown that silicon oxide layers have composition SiO 2 .…”
mentioning
confidence: 98%
“…So, the deposited germanium oxide is substoichiometric, namely GeO x , where x is close to 1 [7]. In [7], it was shown that silicon oxide layers have composition SiO 2 . The set of samples was deposited.…”
mentioning
confidence: 98%
See 2 more Smart Citations